2012
DOI: 10.1155/2012/103973
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol)-Prodrug Conjugates: Concept, Design, and Applications

Abstract: Poly(ethylene glycol) (PEG) is the most widely used polymer in delivering anticancer drugs clinically. PEGylation (i.e., the covalent attachment of PEG) of peptides proteins, drugs, and bioactives is known to enhance the aqueous solubility of hydrophobic drugs, prolong circulation time, minimize nonspecific uptake, and achieve specific tumor targetability through the enhanced permeability and retention effect. Numerous PEG-based therapeutics have been developed, and several have received market approval. A vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
185
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(186 citation statements)
references
References 90 publications
0
185
0
1
Order By: Relevance
“…It has been reported that the physiological activity of α-factor pheromone is closely correlated with affinity for the phospholipid membrane. [36][37][38] Since the target of α-factor is a membrane-associated protein, Ste2p receptor, a certain type of hydrophobic moiety attached to α-factor could aid pheromone localization to the target cell membrane, as do many other hormone such as Ras protein, 29,36-38 thereby leading to increased probability of binding. However, integration of a pheromone into the cellular lipid bilayer depends on the type of modification applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the physiological activity of α-factor pheromone is closely correlated with affinity for the phospholipid membrane. [36][37][38] Since the target of α-factor is a membrane-associated protein, Ste2p receptor, a certain type of hydrophobic moiety attached to α-factor could aid pheromone localization to the target cell membrane, as do many other hormone such as Ras protein, 29,36-38 thereby leading to increased probability of binding. However, integration of a pheromone into the cellular lipid bilayer depends on the type of modification applied.…”
Section: Discussionmentioning
confidence: 99%
“…However, integration of a pheromone into the cellular lipid bilayer depends on the type of modification applied. 21,[36][37][38] Alanine scanning study previously examined the roles of C-and N-terminal residues of α-factor in pheromone activity and receptor binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ideal promoiety remains to be chosen. Poly(ethylene glycol) chains are a strong candidate: their presence can increase aqueous solubility of hydrophobic drugs, prolong circulation time, slow down hydrolysis, and increase stability in the gastrointestinal tract [48][49][50][51][52][53]. This type of decoration is particularly valuable for protein/polypeptide drugs and drug-carrying liposomes (rev.s, e.g., [54][55][56][57][58][59]), which can be protected from phagocytosis and are less at risk of provoking an immune response.…”
Section: Introductionmentioning
confidence: 99%
“…9-11) and gene-directed enzyme prodrug therapy (GDEPT; refs. 6, 12, 13) as well as directly in prodrug monotherapy, which relies on the elevated levels of bG found in the tumor microenvironment (14)(15)(16) to selectively convert prodrug into active drug. For instance, Albin and colleagues reported that the level of bG human breast tumors was up to 6-times greater than that in normal tissues (17).…”
mentioning
confidence: 99%